Effect of doping on the far-infrared intersubband transitions in nonpolar m-plane GaN/AlGaN heterostructures. (23rd February 2016) - Lim, C B; Ajay, A; Bougerol, C; Lähnemann, J; Donatini, F; Schörmann, J; Bellet-Amalric, E; Browne, D A; Jiménez-Rodríguez, M; Monroy, E
Abstract: This paper assesses the effects of Si doping on the properties of nonpolar m -plane GaN/AlGaN quantum wells (QWs) designed for intersubband (ISB) absorption in the far-infrared spectral range. For doping levels up to 3 × 10 12 cm −2, structural analysis reveals uniform QWs with abrupt interfaces and no epitaxially induced defects. Cathodoluminescence spectroscopy confirms the homogeneity of the multiple QWs along the growth direction. Increasing the doping density in the QWs from 1 × 10 11 cm −2 to 3 × 10 12 cm −2 induces a broadening of the photoluminescence as well as a reduction of the exciton localization energy in the alloy. Also, enhancement of the ISB absorption is observed, along with a blue shift and widening of the absorption peak. The magnitude of the ISB absorption saturates for doping levels around 1 × 10 12 cm −2, and the blue shift and broadening increase less than theoretically predicted for the samples with higher doping levels. This is explained by the presence of free carriers in the excited electron level due to the increase of the Fermi level energy.